Dog Man : Grime and punishment - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (New York, NY : Graphix, an imprint of Scholastic, 2020)
"The Supa Buddies bamboozled the baddies, but all's not right in the world. Dog Man has a new problem to pound, and he's going to need his entire pack to help him. Will he go barking up the wrong tree?"--OCLC.
3.5
3-6.
3-6
Keywords: Cats -- Comic books, strips, etc -- Juvenile fiction; Dogs -- Comic books, strips, etc -- Juvenile fiction; Humorous stories; Police -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cats -- Fiction; Dogs -- Fiction; Humorous stories; Police -- Fiction; Cats -- Comic books, strips, etc -- Fiction; Dogs -- Comic books, strips, etc -- Fiction; Humorous graphic novels; Police -- Comic books, strips, etc -- Fiction; Funny animal comics; Graphic novels; Humorous comics